Analisis Kritis Optimalisasi Potensi Digitalisasi Layanan Sesuai Karakteristik Masyarakat dan Demografi Wilayah Provinsi Sumatera Utara - Hutabarat, Ali Yunan (JURNAL ILMIAH GEMA PERENCANA, 2024)
Digitalization of services is one of the national priority programs, but not all work units can implement this program optimally according to performance targets. One indicator of the failure of digital implementation in public services is the small number of users of digital services compared to conventional services. The purpose of this analysis is to carry out a description and analysis of the digitization of services in all work units within the Regional Office of the Ministry of Religious Affairs of North Sumatra Province and to carry out an analysis of several alternative policies to be used as policies that can be implemented in all regions in North Sumatra Province. This analysis was carried out using a qualitative approach, and analyzed using SWOT analysis. The results of this analysis are: 1) Failure in service digitization policies making have an impact on policy implementation that is not optimal as contained in the output and outcomes in the Strategic Plan; 2) The solution to failure in policy making can be policy updates using SWOT analysis with policy making priorities in accordance with Quadrant II, namely maximizing potential (strength) to minimize threats. Conclusion: policy making is not just the result of thinking by outlining the programs contained in planning documents but requires valid, reliable supporting data and academic analysis.